Efektivitas Kombinasi Filtrasi dan Adsorbsi Menggunakan Green Media untuk Mengolah Parameter Organik, Besi dan Mangan Di Sidoarjo - Mas'ulah, Silvi; Hendrasarie, Novirina (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Groundwater is usually use for water for the community, both residential and industrial use. The method for taking groundwater is done using dug wells and drilled wells through electric pumps or manually using buckets. But, actually not all groundwater has good quality. However, groundwater often has a high content of substances in it such as TDS, TSS, iron or manganese that all have an impact to the quality of clean water. So, it is important to process the groundwater first so that it is safe to use for daily needs and to reduce the high content of hazardous substances in it. Just like in this study which about to test the effectiveness process of aeration-filtration and aeration-adsorption processing and the media used from filtration and adsorption in reducing the content of TDS, TSS, iron, manganese, to TOC in drilled well water. In addition, there are also other variations used besides the media, namely variations in contact time for 2, 3, to 4 hours in filtration and adsorption to see the effectiveness of each media that use to in reducing parameters. This research can be the basis for household-scale water purification and filtration methods by utilizing natural materials that are often found in the surrounding area and with simple methods.